Challenges of having a child with thalassemia in Pakistan: A phenomenological study - Rehman, Inayat Ur; Khan, Tahir Mehmood; Bukhsh, Allah; Munawar, Khadeeja; Suleiman, Amal K; Long, Chiau Ming *; Chooi, Wen Han; Al-Worafi, Yaser Mohammed; Tahir, Humera; Fahad, Riaz Choudhry (Elsevier, 2023)
Background: Thalassemia is a persistent hemolytic disease and has debilitating effects on patients and their parents. Parents of these children experience pain and suffer from additional emotional strain as they provide daily and lifetime care and are mostly concerned about the health and future of their children.